Analysis of Vegetation in Green Open Space of Gasing Industrial Area - Siti Indah Oktaviani; Laila Hanum; Zaidan P Negara (Science and Technology Indonesia, 2018)
The study aims to determine the diversity of vegetation in the Green Open Space of the Gasing Industrial Area. The study was conducted from April to July 2017. The method of analysis used quadratic method with 2 plots at different location with three repetitions, quantitative data analysis was done on density value, dominance, frequency, important value and diversity index of each plant species. The results showed that vegetation consists of 16 tribes and 19 species, dominated by Pteridophyta and Spermatophyta. Value of vegetation diversity (2,24) and uniformity value 0,30. The higher number of the species, the higher diversity index of the species. Such characteristics are caused by environmental influences such as organic matter content and low pH and factors derived from human intervention. Keywords: Vegetation, Diversity, industrial area